Medication Reconciliation - A patient safety strategy - Jacson Mandumpala, Janice (Indian Journal of Pharmacy & Drug Studies, 2023)
Patient safety is an international concern and mandates the attention of healthcare professionals. Recently, it has been recognized that multiple strategies and members of the healthcare team from the treating physician to the dispensing pharmacist have a key role to play in assuring patient safety. One such role is that of the clinical pharmacist and the medication reconciliation conducted by them. It is done to get a thorough understanding of the patient medical history, medication history, drug allergy history and many others that could be a loophole for patient harm. This review summarizes a brief review about what is patient safety, and the patterns of employing medication reconciliation in different clinical scenarios that is the emergency department, in transitions of care and in geriatric care. It is specifically important to address the role of growing technology in the same field and so we have also enlisted the ongoing efforts done in the same domain. This review also addresses the role of clinical pharmacists and their emerging responsibility in maintaining a patient safety culture.